Acute Coronary Syndromes and SARS-CoV-2 Infection: Results From an Observational Multicenter Registry During the Second Pandemic Spread in Lombardy - Ferlini, Marco; Castini, Diego; Ferrante, Giulia; Marenzi, Giancarlo; Montorfano, Matteo; Savonitto, Stefano; D’Urbano, Maurizio; Lettieri, Corrado; Cuccia, Claudio; Marino, Marcello; Visconti, Luigi Oltrona; Carugo, Stefano (Frontiers in Cardiovascular Medicine, 2022)
Background. The coronavirus disease 2019 (COVID-19) had an adverse impact on management and outcome of acute coronary syndromes (ACS), but most available data refer to March-April 2020. Aim. To investigate clinical characteristics, time to treatment and clinical outcome of patients hospitalized at hospitals serving as Macro-Hubs during the second pandemic wave of SARS-CoV-2 (November 2020-January 2021). Methods and Results. Nine out of thirteen “Macro-Hubs” agreed to participate to the registry with a total of 941 patients included. The median age was 67 years (IQR 58-77) and ST elevation myocardial infarction (STEMI) was the clinical presentation in 54% of cases. Almost all patients (97%) underwent coronary angiography, with more 60% of patients transported to a Macro-Hub by the Emergency Medical Service (EMS). In the whole population of STEMI patients, the median time from symptom- onset to First Medical Contact (FMC) was 64 minutes (IQR 30-180). The median time from FMC to CathLab was 69 minutes (IQR 39-105). A total of 59 patients (6.3%) presented a concomitant confirmed SARS-CoV-2 infection, and pneumonia was present in 42.4% of these cases. No significant differences were found between STEMI patients with and without SARS-CoV-2 infection in treatment time intervals. Patients with concomitant SARS-CoV-2 infection had a significantly higher in-hospital mortality compared to those without (16.9% versus 3.6%, P<0.0001). However, post-discharge to six-month mortality was similar (4.2% vs 4.1%, P=0.98). At multivariate analysis SARS-CoV-2 infection did not show an indipendent association with in-hospital mortality, whereas pneumonia had a higher mortality (OR 5.65, P 0.05). Conclusion. During the second wave of SARS-CoV-2 infection almost all ACS patients received coronary angiography for STEMI with an acceptable time delay. Patients with concomitant infection presented a lower in-hospital survival with no difference in post discharge mortality; infection by itself was not an independent predictor of mortality whereas pneumonia did.